Alpha suppression and connectivity modulations in left temporal and parietal cortices index partial awareness of words - Magazzini, Lorenzo (Neuroimage, 2016)
The partial awareness hypothesis is a theoretical proposal that recently provided a reconciling solution to graded and dichotomous accounts of consciousness. It suggests that we can become conscious of distinct properties of an object independently, ranging from low-level features to complex forms of representation. We investigated this hypothesis using classic visual word masking adapted to a near-threshold paradigm. The masking intensity was adjusted to the individual perception threshold, at which individual alphabetical letters, but not words, could be perceived in approximately half of the trials. We confined perception to a pre-lexical stage of word processing that corresponded to a clear condition of partial awareness. At this level of representation, the stimulus properties began to emerge within consciousness, yet they did not escalate to full stimulus awareness. In other words, participants were able to perceive individual letters, while remaining unaware of the whole letter strings presented. Cortical activity measured with MEG was compared between physically identical trials that differed in perception (perceived, not perceived). We found that compared to no awareness, partial awareness of words was characterized by suppression of oscillatory alpha power in left temporal and parietal cortices. The analysis of functional connectivity with seeds based on the power effect in these two regions revealed sparse connections for the parietal seed, and strong connections between the temporal seed and other regions of the language network. We suggest that the engagement of language regions indexed by alpha power suppression is responsible for establishing and maintaining conscious representations of individual pre-lexical units.